Analytical and numerical methods for estimating the probability of interlaminar fracture in Mode I of composite structures under the peel test - Benchaib, Nadia; Mechab, Belaïd; Medjahdi, Malika; Metehri, Aicha; Salem, Mokadem; Bachir Bouiadjra, Bel Abbes (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The present work utilizes a numerical and analytical approach to predict the likelihood of interlaminar fracture in Mode I of a composite structure under the peel test.Methods:The finite element approach, which incorporates the Virtual Crack Closure (VCCT) method, is utilized to examine the delamination of the composite structure. The research investigated the effects of many aspects, including dimension, fiber alignment, and composite properties.Results: The numerical results significantly concur with the analytical solution recorded in the current body of literature. The Monte Carlo technique predicts the distribution function of composite damage. As previously stated, the probability of structural failure is assessed by considering both the model's uncertainty and the statistical uncertainty linked to the essential variables. Conclusion: The probability density function (pdf) is derived by fitting specific theoretical models to the histogram. The durability of composite structures is primarily dependent on their mechanical properties.
Keywords: composite; delamination; peel test; VCCT method; durability